Rietveld Structure Refinement of Cu-Trien Exchanged Nontronites - Wang, Xiaoli; Liao, Libing (Frontiers in Chemistry, 2018)
The Rietveld analysis of X-ray powder diffraction patterns is widely used for obtaining the structural information of clay minerals. However, the complex hydration behavior and the variability of interlayer contents are commonly considered difficult to be described correctly by a simple structure model. In the present work, the use of Cu-triethylenetetramine (Cu-trien) exchanged nontronites has been proposed to simplify the interlayer structure. This method provides a potential to obtain the structural information of nontronites, e.g. the layer charge density, occupancies of cis-octahedral sites and iron content by the Rietveld analysis from the X-ray powder diffraction patterns. The approach was demonstrated on three Cu-trien exchanged nontronite samples. The Rietveld refinements were firstly carried out on the purified samples and the results showed a good peak fitting between measured and calculated patterns. The refined iron content and the occupancies of cis-octahedral sites are in general agreement with the reference data which obtained from chemical and thermal analysis. The refinement of layer charge density showed lower values compared to the reference. It may due to the assumption of temperature factor of Cu-trien in the interlayer. A raw sample with natural impurities was chosen to test the applicability of this method. The refinement pattern of the raw sample led to good agreement with the observed data. The results of the iron content and the occupancies of cis-octahedral sites showed same tendency as purified sample. This study was shown that this approach allows for obtaining some structural details of nontronites directly from X-ray powder diffraction patterns of Cu-trien exchanged samples.